How to Create a New Holiday Destination? An Evaluation of Local Public Investment for Supporting Tourism Industry in Regions Lagging Behind - Martin Rosenfeld; Albrecht Kauffmann (European Regional Science Association (ERSA), 2010)
In many European regions, globalization and interregional competition have resulted in a collapse of old traditional industries and strong economic development problems. Policymakers in some of these regions are trying to change the path of development in the direction to attract businesses from the field of tourism, in many cases with the help of money from the national government or the EU-level. The general question is whether this strategy could be successful. The paper reports on an empirical study for the German state of Saxony. In many Saxonian regions, following the German re-unification, a strong de-industrialization has taken place. Since the 1990s, in Saxony, the field of tourism had been one major sector for creating new local infrastructure. E. g. in areas with exhausted opencast workings, where the mining industry had formerly been the main source of income, policymakers have begun to change the region into a new lake district and to build infrastructure like waterways, marinas etc. Millions of Euros have been spent to build new bike paths throughout the state or to construct completely new local tourist attractions. The paper's first section gives an overview on tourism industry in Saxony and on public investment in infrastructure for supporting this sector. The second section has the task to identify specific location factors which are relevant for tourism industry. This is done on the base of existing theoretical and empirical studies. The third section is evaluating the impact of public investments for supporting tourism industry in different parts of Saxony; this is based on quantitative data and qualitative interviews with local experts. One major result is that infrastructure in the field of tourism may only have positive effects on regional development if a region is well-equipped with relevant complementary factors, e. g. with a service-oriented mentality within the population. In many cases, the grants from the national to the local level have been spent for infrastructure which is mainly used by the local population, not by tourists.
Keywords: 330